Materials for Architects & Builders / Third Edition - Lyons Arthur (Elsevier, 2007)
This book provides an introduction to a wide range of building materials. The book also describes many recent technological innovations and rediscovered materials, reflecting an increased concern for environmental issues within the industry. Bricks and Brickwork, Blocks and Blockwork, Lime and Cement and Concrete, Timber and Timber Products, Ferrous and non-Ferrous Metals, Bitumen and Flat Roofing Materials, Glass, Ceramic Materials, Stone and Cast Stone, Plastics, Glass-Fibre Reinforced Plastics, Plaster and Board Materials, Insulation Materials, Energy-saving Materials and Components, Recycled and Ecological Materials, Sealants and Gaskets and Adhesives, Paints and Wood Stains and Varnishes.